EFFICIENT SYNTHETIC DYES DECOLORIZATION USING MAGNETIC NANOPARTICLE CROSS-LINKED AGGREGATE OF ASPERGILLUS FLAVUS KIGC LACCASE (Nigerian Journal of Technology, 2025)
The study evaluated the synthesis, characterization and synthetic dye decolorization potential of iron oxide nanoparticle immobilized laccase extracted from Aspergillus sp KIGC. Laccase was extracted from fungal isolate on Day 8 of submerged fermentation process, with bambara nut husk and soybean extract as sole carbon and nitrogen sources, respectively at pH 6.5. The enzyme was purified to 2.55 folds and 68.90% purification yield, with an SDS-PAGE gel that showed a band corresponding to 66 KDa, indicating a monomeric enzyme. The immobilization of Aspergillus sp KIGC laccase on iron oxide nanoparticle chemically modified and functionalized by amino-prolyltri-ethoxysilane/glutaraldehyde was evaluated. DLS, DSC, XRD, FTIR and SEM were the instruments used in the characterization of the synthesized and immobilized paramagnetic nanoparticles. There was effective nanoparticle synthesis and adequate laccase immobilization on the nanoparticle as evidenced by the characterization results obtained. Immobilization improved the enzyme’s catalytic properties (KM (1.04 mM) and catalytic efficiency (13.308 mol/S-1) more than the free enzyme (1.971 mol/S-1), with the concomitant high dye decolorization efficiency (75% decolorization rate). The results show the production of laccases using cheap and readily available agro-residues at relatively mild submerged fermentation conditions from Aspergillus sp KIGC and the high decolorization potential of immobilized laccase on iron oxide nanoparticle, as a promising biocatalyst that could be used in treating (decolorizing) wastewater containing synthetic dyes.